1987
DOI: 10.1177/00220345870660090901
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Ferromagnetic Alloys used for Magnetic Retention of Overdentures

Abstract: Three ferromagnetic casting alloys intended for use with magnetically retained overdentures (compositions in wt%: #1, Pd 50, Co 47, Ga 2, Pt 1; #2, Pd 60, Co 37, Ga 2, Pt 2; #3, Pd 49, Co 46, Ga 2, Pt 2) were investigated. A 0.9% saline solution and an artificial saliva (Meyer) were used for evaluation of the electrochemical corrosion behavior of these alloys, utilizing standard potentiodynamic techniques. All alloys investigated possessed a good corrosion resistance in the potential range of the oral environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 5 publications
1
16
0
2
Order By: Relevance
“…Chemical composition of alloy Starting with an alloy's chemical composition, some alloying elements are known by their lability more than other elements. Some alloying combinations may result in synergistic effects which alter the elements' lability and thus increase or decrease the ion release rate 2,3,5,6,22,28,29) . Ni, Cr, Mo, and Co had a decreasing effect on the corrosion rate of base metal alloys 5,17,24,[30][31][32] , whereas Fe had an increasing effect 10,24) .…”
Section: Factors Related To Ion Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Chemical composition of alloy Starting with an alloy's chemical composition, some alloying elements are known by their lability more than other elements. Some alloying combinations may result in synergistic effects which alter the elements' lability and thus increase or decrease the ion release rate 2,3,5,6,22,28,29) . Ni, Cr, Mo, and Co had a decreasing effect on the corrosion rate of base metal alloys 5,17,24,[30][31][32] , whereas Fe had an increasing effect 10,24) .…”
Section: Factors Related To Ion Releasementioning
confidence: 99%
“…Many studies have reported on the release of metallic ions from high-noble, noble, and base dental casting alloys under differing pH conditions which simulated the oral cavity 2,3) . A low pH environment (i.e., acidic conditions) increases the release of metallic ions from dental alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems like the locator and metal bar are less likely to wear over time, even after the simulation of 5000 cycles of insertion [21]. Therefore, they should have a better clinical outcome than ball attachments and magnets [10,11,21,27]. In a clinical trial, it has been reported that the locator and ball attachments need to be replaced with almost the same frequency [24].…”
Section: Discussionmentioning
confidence: 99%
“…Duomagnetic systems (magnet + magnet) instead are ones in which one magnet (the primary one) is placed on the implant, and a second one (the secondary one) is placed on the prosthesis, as for example the Steco Titanmagnetics ® and MicroPlant ® . Despite the improvements in the structure, in the oral cavity environment they are subject to corrosion, reducing their retentive capabilities in the long-term [10,11]. This system should be limited to use in cases of reduced vertical space available for the attachment.…”
Section: Magnetsmentioning
confidence: 99%